Robust fuzzy 3D path following for autonomous underwater vehicle subject to uncertainties - Xiang, Xianbo; Yu, Caoyang; Zhang, Qin (Computers & operations research, 2017)
This paper addresses a three-dimensional (3D) path following control problem for underactuated autonomous underwater vehicle (AUV) subject to both internal and external uncertainties. A two-layered framework synthesizing the 3D guidance law and heuristic fuzzy control is proposed to achieve robust adaptive following along a predefined path. In the first layer, a 3D guidance controller for underactuated AUV is presented to guarantee the stability of path following in the kinematics stage. In the second layer, a heuristic adaptive fuzzy algorithm based on the guidance command and feedback linearization Proportional-Integral-Derivative (PID) controller is developed in the dynamics stage to account for the nonlinear dynamics and system uncertainties, including inaccuracy modelling parameters and time-varying environmental disturbances. Furthermore, the sensitivity analysis of the heuristic fuzzy controller is presented. Against most existing methods for 3D path following, the proposed robust fuzzy control scheme reduces the design and implementation costs of complicated dynamics controller, and relaxes the knowledge of the accuracy dynamics modelling and environmental disturbances. Finally, numerical simulation results validate the effectiveness of the proposed control framework and illustrate the outperformance of the proposed controller as well. •A two-layered framework synthesizing the guidance and control is proposed for 3D AUV path following.•Robust and heuristic fuzzy path following algorithm is adopted to account for the system uncertainties.•Proposed control scheme reduces the design and implementation cost with regard to most existing methods.•Case study and quantitative comparison explicitly show the effectiveness of the proposed framework.